Infaq and Shadaqah for Education: Prohibited Fees or Social Responsibility? Infaq dan Shadaqah untuk Pendidikan: Biaya yang Dilarang atau Tanggung Jawab Sosial? - Suryani Indah; Rifqi Ridlo Phalevy (Academia Open, 2023)
This research aims to analyze the relationship between voluntary donations (infaq) and prohibited fees in the Ministry of Education and Culture Regulation No. 44 of 2012, as well as the views of Islamic scholars regarding the position of voluntary donations as a means of financing education. The research method used is a normative approach that utilizes legal and comparative approaches. The research findings indicate that voluntary donations, also known as infaq, shadaqah, or amal jariyah, are considered a prohibited fee under the Ministry of Education and Culture Regulation No. 44 of 2012. However, in practice, these voluntary donations meet the criteria for fees as described in Article 11 of the regulation and are viewed by Islamic scholars as a form of social responsibility in the field of education. It is not permissible for these donations to be binding on the donor in terms of the amount and time of donation. Highlights : This research examines the connection between voluntary donations (infaq) and prohibited fees in education financing under Ministry of Education and Culture Regulation No. 44 of 2012. The findings show that although infaq is considered a prohibited fee, it is viewed as a form of social responsibility in education by Islamic scholars. It should not be binding on the donor in terms of the amount and time of donation. Keywords: infaq, shadaqah, voluntary donations, education financing, Islamic scholars.